Separation and modification of lignin from oil palm empty fruit bunch and its application as a phenolic lignin adhesive in wood composites - Farhana, Sultana Toma (2023)
Lignin is a polyphenolic molecule that can be used as a partial phenol substitution in phenolic resin compositions. Due to the phenolic structure and huge available quantities of lignin, lignin is an excellent bio-based component for phenol substitution in phenolic resin. However, the reactivity of lignin is low with formaldehyde when phenol formaldehyde (PF) resin is prepared. The present work aims to increase the lignin reactivity by chemical modification (phenolation) and utilize the lignin and modified lignin as a partial substitute for phenol in PF wood adhesive. In this work, lignin was extracted by the kraft pulping process from oil palm empty fruit bunch (OPEFB), and the extracted lignin is known as kraft lignin (KL). In the kraft pulping method, two solvents were used, 19% NaOH and 25% Na2S based on raw materials, with fiber to solvent ratio of 1:8, the pulping temperature and time were 170°C and 3 h, respectively. Then, KL was modified using the phenolation method, in which the KL was reacted with phenol in different ratios (1:1, 1:1.5, and 1:2) in an acidic medium (H2SO4), resulting in a considerable drop in aliphatic hydroxyl groups and a rise in phenolic hydroxyl groups of that lignin. For the preparation of phenolated kraft lignin (PKL), the reaction temperature varied from 90 to 130°C, and the reaction time varied from 100 to 140 min. KL and PKL were characterized using FTIR, 1HNMR, and elemental analysis. The physical properties such as moisture, solid, and ash content of KL and PKL were also studied. Both KL and PKL were introduced to the PF resin by substituting a certain percentage (10-50%) of phenol. The synthesized kraft lignin phenol formaldehyde (KLPF) and phenolated kraft lignin phenol formaldehyde (PKLPF) resins were also compared to PF resin. FTIR and DSC were used to characterize all the resins. The physical properties of all resins, such as viscosity, gel time, solid content, free phenol content, and free formaldehyde content, were studied. The water absorption, thickness swelling, formaldehyde emission, and shear strength of the plywood panels bonded with these adhesives were measured according to the standard method. The outcomes demonstrated that the phenolation process improved the lignin's reactivity as well as the PLPF's adhesive properties. The shear strength of plywood bonding with PKLPF resin meets the criteria of the relevant standards specifications and is substantially superior to that of panels bonding with PF resin. The effects of KL and PKL substitutions in resin for shear strength and formaldehyde emission of plywood were studied. The effects of phenol substitution with lignin or phenolated lignin, the hot press temperature and the pressing time were investigated and optimized to obtain the best possible pressing time and temperature for the performance of plywood adhesive. The response surface methodology (RSM) was used to optimize the hot-press temperature and press time for the plywood preparation process. The experiments have been conducted in the pressing time range from 50 s to 250 s and at temperatures ranging from 120 to 200oC. The experimental results showed a significant increase in plywood shear strength and a decrease in formaldehyde emission. The optimized percentage of phenol substitution with PKL in the PF adhesive was 30% and with KL it was 20%. The maximum shear strength of 3.2 MPa and minimum formaldehyde emission of 0.633 mg/L were found in the PKLPF adhesive. This research demonstrated the use of PKL as a renewable replacement of phenol in phenolic resin formulation and strongly suggested that phenolated lignin can be used as a high-value-added product in wood adhesive applications.